Agency Costs, Ownership Structure and Corporate Governance Mechanisms: A Case Study in New Zealand Unlisted Small Companies - Wellalage , Nirosha Hewa; Locke , Stuart (Journal of Law and Governance, 2011)
This study investigates the linkage between agency costs, ownership structure and corporate governance in small business. Eleven years of data for 100 unlisted small businesses, are collected and 1099 observations are analysed using as dynamic panel GMM estimation. Various diagnostic tests are utilised to check for stationary and convergence of variables. The results indicate that ownership concentration has the most significant governance effect and also has the largest impact on corporate governance. Moreover, this study finds U-shape relationship between internal ownership and performance, which under that agency proxy. Agency costs vary with leverage the life of the business and with its size.